2020
DOI: 10.21098/jimf.v6i3.1117
|View full text |Cite
|
Sign up to set email alerts
|

User Acceptance of Online Waqf Application: Evidence From Indonesia

Abstract: Waqf is an Islamic asset endowment to be kept in faith and used for charitable or religious purposes. Its function is to demonstrate the potential and economic benefits of waqf assets for worship and other people’s prosperity. Indonesia has great opportunities to raise more significant amounts of waqf funds. One strategy that appears effective with regard to waqf, especially cash waqf, is to provide an online service. Hence, this research attempts to analyse whether the perceived usefulness, perceived ease of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 15 publications
2
12
1
2
Order By: Relevance
“…Moreover, the trust construct is positioned as a variable to mediate the relationship between perceived ease of use (PEU) and perceived usefulness (PU) in individual intentions to purchase Retail CWLS. This has not been done in previous studies, especially in the context of Islamic philanthropy, both in the empirical study of zakat (Kasri & Yuniar, 2021;Purwanto et al, 2021;Mohd Thas Thaker et al, 2019) and waqf (Berakon et al, 2021;Faturohman et al, 2020).…”
Section: Introduction 11 Backgroundmentioning
confidence: 92%
See 3 more Smart Citations
“…Moreover, the trust construct is positioned as a variable to mediate the relationship between perceived ease of use (PEU) and perceived usefulness (PU) in individual intentions to purchase Retail CWLS. This has not been done in previous studies, especially in the context of Islamic philanthropy, both in the empirical study of zakat (Kasri & Yuniar, 2021;Purwanto et al, 2021;Mohd Thas Thaker et al, 2019) and waqf (Berakon et al, 2021;Faturohman et al, 2020).…”
Section: Introduction 11 Backgroundmentioning
confidence: 92%
“…TAM is widely adopted in various research contexts, especially in studies that analyse the use of financial technology and digital platforms to channel donations, pay zakat and perform waqf online (Faturohman et al, 2020;Niswah et al, 2019;Purwanto et al, 2021;Thaker, 2018). Thaker (2018) found that PEOU had a significant positive effect on the PU of small and medium-sized enterprises in accessing Islamic crowdfunding as a source of financing in Malaysia.…”
Section: Perceived Ease Of Use Perceived Usefulness and Trustmentioning
confidence: 99%
See 2 more Smart Citations
“…Waqf is unique because its characteristics are permanent, inalienable and irrevocable (Hasan and Sulaiman, 2016; Ghazali et al , 2019). The owner’s intention to donate is to obtain rewards from God in the hereafter (Kahf, 2003; Shabbir, 2018; Faturohman et al , 2020; Hasan et al , 2018). The components of waqf could be moveable assets (books, computers, vehicles, shares, stocks and cash) or immovable assets (Mahamood, 2007; Tekdogan, 2020).…”
Section: Introductionmentioning
confidence: 99%